In vitro cytotoxic and non-genotoxic effects of gutta-percha solvents on mouse lymphoma cells by single cell gel (comet) assay - Ribeiro, Daniel Araki [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (FapUNIFESP (SciELO), 2006)
Chloroform and eucalyptol are widely used in clinical dentistry as gutta-percha solvents. However, these compounds may represent a hazard to human health, especially by causing injury to genetic apparatus and/or inducing cellular death. In this study, the genotoxic and cytotoxic potentials associated with exposure to chloroform and eucalyptol were assessed on mouse lymphoma cells in vitro by the single cell gel (comet) assay and trypan blue exclusion test, respectively. Both gutta-percha solvents proved to be cytotoxic at the same levels in concentrations of 2.5, 5 and 10 μL/mL (p<0.05). On the other hand, neither of the solvents induced DNA breakage. Taken together, these results suggest that although both tested compounds (chloroform and eucalyptol) are strong cytotoxicants, it seems that they are not likely to increase the level of DNA damage on mammalian cells.
Keywords: Chloroform; Cytotoxicity; Eucalyptol; Genotoxicity; Mouse lymphoma cells; chloroform; cineole; coloring agent; cyclohexanol derivative; diagnostic agent; DNA; gutta percha; mutagenic agent; solvent; terpene; trypan blue; animal; cell survival; chemistry; comet assay; DNA strand breakage; drug effect; Eucalyptus; leukemia L 5178 Y; mouse; pathology; Animals; Cell Survival; Coloring Agents; Comet Assay; Cyclohexanols; DNA Breaks; Gutta-Percha; Leukemia L5178; Mice; Monoterpenes; Mutagens; Solvents; Trypan Blue